STUDI PEMBUATAN MINUMAN PROBIOTIK DARI SARI UBI JALAR (Ipomoea Batatas) - Mhd. Iqbal Nusa; Syakir Naim Siregar; Iswanil , (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
AbstractThis study aims to determine the effect of the cmc and the starter for the quality of probiotic drinks. This study uses a complete Randomized Design (CRD) with factorial (2) of two replicates. Factor I is the number of CMC with a password (C) which consists of four standards are: C0 = 0%, C1 =0,2%, C2 =0,4% and C3=0.6%. Factor II is the starter with a password (S) consisting of 4 standard, namely S1 = 2%, S2 = 4%, S3 = S4 = 6% and 8%. The parameters observed include: TSS, total acid, organoleptic aroma and flavor. This study uses yellow sweet potato extract as a source of prebiotic, and starter L. casei as a source of probiotics. Sinbiotik fermented milk made from a combination of prebiotics and probiotics with pasteurized milk as a medium (substrate). CMC provides a number of different influences highly significant (P <0.01) for TSS, total acid, organoleptic aroma and flavor. Starter number of different influences highly significant (P <0.01) for TSS, total acid, and organoleptic taste and significantly different (P <0.05) to the organoleptic flavor. Interaction of different treatments did not influence significantly (P> 0.05) for TSS, total acid, organoleptic aroma and flavor.Keywords: prebiotic, probiotic, Ipomoea Batatas, CMC, Lactobacillus casei